TRANSPOSITION IN TRANSLATION: TYPES OF INTERPRETATION IN UZBEK AND ENGLISH - Tulkinova Mamura (American Journals Publishing, 2023)
The topic of conversion translation transposition interpretation in various contexts is the focus of this article. Language units in conversion relations are examined from a variety of angles, and their unique characteristics are discussed. The relationship between conversion transformations and other modifications is examined in the article. Additionally, the impact of intricate translation modifications on conveying the original text's discursive structure in the translation is taken into account.
Keywords: Translation, conversion translation, interpretation, transposition conversion in Uzbek and English and interpretation, discursive form of the text, variant and non-variant forms of translation, complex nature of conversion transformations.